45th Winter School on Wave and Quantum Acoustics and XLIVth Winter School on Environmental Acoustics and Vibroacoustics - 45th Winter School on WQA; XLIVth Winter School on EA&V (Archives of Acoustics)
On behalf of Upper Silesian Division of the Polish Acoustical Society (main organizer) and Committee of Acoustics of the Polish Academy of Sciences (co-organizer) we are pleased to announce that it is nearing the end of preparations for the conduct traditionally organized Conferences, which will take place as previously in Szczyrk. At the moment, more than 50 people have confirmed participation in Conferences. They will present more than 40 lectures and reports.